Exploring gender differences in the vulnerability towards drug abuse among adolescents in Malaysia - Wan Sulaiman, Wan Shahrazad; Kamaluddin, Mohammad Rahim; Zakaria, Ezarina; Ibrahim, Fauziah; Hassan, Nazirah; Manap, Jamiah; Nen, Salina; Ahmad Zamani, Zainah; Yusooff, Fatimah (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Protective and risk factors are important issues to consider to reduce the vulnerability of adolescents to drug abuse. This study aims to determine the vulnerability to drug abuse in terms of gender differences in high-risk areas, based on statistics/data from the National Anti Narcotics Agency of Malaysia, namely in Sabak Bernam, Dungun, Johor Bahru, and Kuala Kedah. A survey method was employed, with 213 adolescents (52.1% male, 47.9% female) who met the inclusion criteria completing the questionnaire. The questionnaire consisted of five aspects, namely demographic profile, interpersonal conflict, negative emotions, social support, and mental health. Data analysis was conducted using descriptive and inferential statistics. The results of the analysis show that there was no significant difference in aspects of interpersonal conflict (t=-0.556, p > .05), negative emotions (t=0.131, p>.05), or mental health by gender (t=-0.898, p > .05). However, there was a significant difference in the aspect of social support (t=-2.046, p <.05), with female subjects (37.13) showing a higher mean score than males (34.83). The findings of the study indicate that it is very important to understand the relevant factors so that drug abuse can be identified and prevented early on.